Hubungan Hasil Belajar Produk Kreatifitas dan Kewirausahaan (PKK) dengan Minat Berwirausaha Siswa Teknik Pemesinan SMS Dhuafa Padang - Kurniawan, Ridho; Yufrizal, Yufrizal; Kurniawan, Andre; Wulansari, Rizky Ema (Lembaga Yasin AlSys, 2024)
SMKS Dhuafa Padang equips students with entrepreneurial knowledge and skills through the subject of Creativity Products and Entrepreneurship (PKK) However, students' interest in entrepreneurship is still low. This study examines the factors behind it, such as the increasingly narrow job opportunities, Entrepreneurship can create jobs, PKK has an influence on the entrepreneurial spirit, Entrepreneurship learning has an important role in increasing students' entrepreneurial interest. This study uses a quantitative correlational type to determine the relationship between PKK and Entrepreneurial Interest. Data collected in the form of numbers and analyzed using statistics. The research method used is associative quantitative, which aims to determine the influence and relationship between PKK and Entrepreneurial Interest. The study found that PKK has a relationship with students' interest in entrepreneurship at SMKS Dhuafa Padang. This is evidenced through the T test and F test, where the value of Sig. 0.05 and the value of tcount ttable (in the T test) and the value of fcount ftable (in the F test) indicate a relationship. In conclusion, PKK proved to play an important role in increasing students' interest in entrepreneurship, with 29.2% influenced by PKK and the rest by other factors.